A Feature of Dissemination of Buddhism on Social Media: The Strength and the Weakness - คุณากโร (อัญโญ) พระมหาสมพงษ์ (วารสารพุทธอาเซียนศึกษา, 2023)
The feature of discrimination of Buddhism is gradually changed which depends on the changing society and its environment. Regarding the discrimination of Buddhism, from Buddha’s period to the period of IT by using social media with internet access, it indicates the different way thereof. On Buddha’s period, Buddha and his disciples preferred propagating Buddhism by approaching the people directly by travelling from city to city, village by village, etc. By the period after Buddhist council, seemingly, the strategy of such this discrimination is not much different from Buddha’s period as a missionary monk also preferred travelling for directly giving a sermon to people at different places, but beyond the India to abroad that make Buddhism spreading to other places widely. In the period of social media, religious people, whether monks, laities or religious organization, prefer using social media to disseminate Buddhism by utilizing the high technology as a tool for such this purpose that is internet connection. With this, Buddhism has fast penetrated through every corner of the world wherever internet access is available and people therein comfortably learn Buddhism.